Microtubule-severing ATPase spastin in glioblastoma: increased expression in human glioblastoma cell lines and inverse roles in cell motility and proliferation - Dráberová, Eduarda; Vinopal, Stanislav; Morfini, Gerardo; Liu, Pei S; Sládková, Vladimíra; Sulimenko, Tetyana; Burns, Matthew R; Solowska, Joanna; Kulandaivel, Kandan; de Chadarévian, Jean-Pierre; Legido, Agustin; Mörk, Sverre J; et al. (Journal of neuropathology and experimental neurology, 2011)
We studied the expression and distribution of the microtubule-severing enzyme spastin in 3 human glioblastoma cell lines (U87MG, U138MG, and T98G) and in clinical tissue samples representative of all grades of diffuse astrocytic gliomas (n = 45). In adult human brains, spastin was distributed predominantly in neuronsand neuropil puncta and, to a lesser extent, in glia. Compared with normal mature brain tissues, spastin expression and cellular distribution were increased in neoplastic glial phenotypes, especiallyin glioblastoma (p < 0.05 vs low-grade diffuse astrocytomas). Overlapping punctate and diffuse patterns of localization wereidentified in tumor cells in tissues and in interphase and mitotic cells ofglioblastoma cell lines. There was enrichment of spastin in the leading edges of cells in T98G glioblastoma cell cultures and in neoplastic cell populations in tumor specimens. Real-time polymerase chain reaction and immunoblotting experiments revealed greater levels of spastin messenger RNA and protein expression in theglioblastoma cell lines versus normal human astrocytes. Functional experiments indicated that spastin depletion resulted in reduced cell motility and higher cell proliferation of T98G cells. Toour knowledge, this is the first report of spastin involvement incellmotility. Collectively, our results indicate that spastinexpression in glioblastomas might be linked to tumor cell motility, migration, and invasion.
Keywords: regulace genové exprese u nádorů; Cell Count; proliferace buněk; Female; Infant; dítě; mikrotubuly; Cell Line, Tumor; Age Factors; ženské pohlaví; mladý dospělý; Gene Expression Regulation, Neoplastic; věkové faktory; nádory mozku; lidé; adenosintrifosfatasy; messenger RNA; mozek; glioblastom; Glioblastoma; pohyb buněk; RNA, Messenger; Male; kojenec; Brain; Young Adult; Brain Neoplasms; Cell Proliferation; počet buněk; Microtubules; lidé středního věku; Child; Cell Movement; mužské pohlaví; Adenosine Triphosphatases; Middle Aged; nádorové buněčné linie; Humans